Effect of laparoscopic abdominal surgery on splanchnic circulation: - Hatipoglu, S; Akbulut, S; Hatipoglu, F; Abdullayev, R (2014)
With the developments in medical technology and increased surgical experience, advanced laparoscopic surgical procedures are performed successfully. Laparoscopic abdominal surgery is one of the best examples of advanced laparoscopic surgery (LS). Today, laparoscopic abdominal surgery in general surgery clinics is the basis of all abdominal surgical interventions. Laparoscopic abdominal surgery is associated with systemic and splanchnic hemodynamic alterations. Inadequate splanchnic perfusion in critically ill patients is associated with increased morbidity and mortality. The underlying pathophysiological mechanisms are still not well understood. With experience and with an increase in the number and diversity of the resulting data, the pathophysiology of laparoscopic abdominal surgery is now better understood. The normal physiology and pathophysiology of local and systemic effects of laparoscopic abdominal surgery is extremely important for safe and effective LS. Future research projects should focus on the interplay between the physiological regulatory mechanisms in the splanchnic circulation (SC), organs, and diseases. In this review, we discuss the effects of laparoscopic abdominal surgery on the SC. (C) 2014 Baishideng Publishing Group Inc. All rights reserved. C1 [Hatipoglu, Sinan] Adiyaman Univ, Fac Med, Dept Surg, TR-02040 Adiyaman, Turkey. [Akbulut, Sami] Inonu Univ, Fac Med, Dept Surg, TR-44280 Malatya, Turkey. [Akbulut, Sami] Inonu Univ, Fac Med, Liver Transplant Inst, TR-44280 Malatya, Turkey. [Hatipoglu, Filiz] Adiyaman Univ, Fac Med, Dept Obstet & Gynecol, TR-02040 Adiyaman, Turkey. [Abdullayev, Ruslan] Adiyaman Univ, Fac Med, Dept Anesthesiol & Reanimat, TR-02040 Adiyaman, Turkey.